The Asphalt has arrived - Ramos, M. (Moving Africa, 2011)
This short video was presented as part of a paper presented at the panel "Moving Africa", dedicated to the case study of Gonder city, in the North Amhara region, in Ethiopia. Gonder, the ancient royal capital of the Abyssinian kingdom, is presently home to a monumental architectural complex listed as a world heritage site by UNESCO. The paper analyzed the existing tensions between the city administration's commitments to preserve this site while looking for the tourist industry for way to develop its economy, and at the same time juggling the city's social and spatial "pre-modern" morphology with a recent appetite for modernizing its urbanism and road network - namely since the 2003 revision of the city's old master plan produced by the Italian military engineers and architects, during the period of Italy's invasion of the country, in the late nineteen thirties'. The need, or rather the will of the local administration to adapt the city to growing automotive traffic, is thus simultaneous with a new stage of its touristic development, which took off with the end of the Ethio-Eritran war and with the expanding afflux of the Gondarine diaspora living in Europe and in the USA. This trend clashes directly with still common practices of living the city's public spaces that are mainly pedestrian. The resulting situation is one of increasing conflict between motorized traffic and pedestrian circulation, shaped by a clear option of the local authorities to give precedence to the former and disregarding the needs of the latter. The video was shot in December 2008, in a street leading to Djenjabet Maryam's church (in the royal compund), during paving procedures that would irreversibly change the neighbourhood's landscape and people's daily life.